DsFoxO knockout affects development and fecundity of Drosophila suzukii - Zhao, Shan; Wang, Ruijuan; Liu, Yan; Su, Long; Dai, Xiaoyan; Qin, Dongyun; Chen, Hao; Yin, Zhenjuan; Zheng, Li; Zhai, Yifan (Frontiers in Physiology, 2023)
Forkhead box O (FoxO), a key transcription factor in many species, participates in numerous physiological and pathological processes of organisms through a variety of signaling pathways. In present study, we evaluated the influence on development and fecundity of Drosophila suzukii when knocking out DsFoxO. DsFoxO-KO strain was established using CRISPR/Cas9 and the results of life history traits analysis showed that the survival rates of DsFoxO-KO strain in stage larva, pupa and adult were all significantly lower than control. The duration of pupa stage was similar between the two strains, however, durations of egg, larva, adult preoviposition period (APOP) and total APOP (TPOP) in DsFoxO-KO strain were all significantly longer compared to control strain. The fecundity of DsFoxO-KO strain was 20.31 eggs/female, which was significantly lower than control strain (430.47 eggs/female). Subsequently, a transcriptome analysis was conducted and 612 differentially expressed genes (DEGs) were identified. Following COG and GO analyses, we found that most of the DEGs were associated with metabolic process. According to KEGG database, mTOR signaling pathway, MAPK signaling pathway, Wnt signaling pathway, Toll and Imd signaling pathway, insect hormone biosynthesis, autophagy and apoptosis were altered in DsFoxO-KO strain. These results demonstrated that knockout of DsFoxO in D. suzukii significantly influenced its development and fecundity, while transcriptome analysis provided insights to explore the corresponding molecular mechanism. These findings highlighted the critical role of FoxO in D. suzukii and might contribute to the development of novel management strategies for these flies in the future.